2020
DOI: 10.5194/acp-2019-1176
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Observation of absorbing aerosols above clouds over the South-East Atlantic Ocean from the geostationary satellite SEVIRI – Part 2: Comparison with MODIS and aircraft measurements from the CLARIFY-2017 field campaign

Abstract: <p><strong>Abstract.</strong> To evaluate the SEVIRI retrieval for aerosols above clouds presented in Part 1 of the companion paper, the algorithm is applied over the South East Atlantic Ocean during the CLARIFY-2017 field campaign period. The first step of our analysis compares the retrieved aerosol and cloud properties against equivalent products from the MODIS MOD06ACAERO retrieval (Meyer et al., 2015). While the correlation between the two satellite retrievals of t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 37 publications
(53 reference statements)
2
15
0
Order By: Relevance
“…Our paper is focused on instantaneous DARE and stops short of providing an "all-ORACLES" (diurnally integrated) DARE estimate. A promising approach in this regard is to use geostationary satellite retrievals of cloud and aerosol properties (Peers et al, 2020) in conjunction with in situ aircraft data and radiative transfer calculations. Alternatively, one can use the satellite radiances to extrapolate from the spatially and temporally limited aircraft observations to obtain regional estimates of the diurnally integrated DARE, circumventing the satellite retrievals.…”
Section: Dare Parameterizationsmentioning
confidence: 99%
“…Our paper is focused on instantaneous DARE and stops short of providing an "all-ORACLES" (diurnally integrated) DARE estimate. A promising approach in this regard is to use geostationary satellite retrievals of cloud and aerosol properties (Peers et al, 2020) in conjunction with in situ aircraft data and radiative transfer calculations. Alternatively, one can use the satellite radiances to extrapolate from the spatially and temporally limited aircraft observations to obtain regional estimates of the diurnally integrated DARE, circumventing the satellite retrievals.…”
Section: Dare Parameterizationsmentioning
confidence: 99%
“…SEVI-RI shows the largest bias due to significantly underestimated COD retrievals, particularly for larger SSFR CODs. Peers et al (2021) also found a lower mean COD from SEVIRI than MODIS Meyer at a 0.1° spatial resolution comparison over the southeast Atlantic in August and September 2017, especially for larger COD values.…”
Section: Evaluation Of Cod From Modis and Seviri Against The Ssfr And Impacts Of Temporal Collocationmentioning
confidence: 64%
“…These shortcomings have motivated the algorithm development of ACAOD products (e.g., Jethva et al, 2013;Meyer et al, 2013Meyer et al, , 2015Sayer et al, 2016) and ACAOD intercomparisons among active and passive satellite platforms (e.g., Deaconu et al, 2017;Jethva et al, 2014). Airborne measurements useful for satellite ACAOD evaluations were limited prior to the recent field deployments over the southeast Atlantic (e.g., Jethva et al, 2016;Sayer et al, 2016), but the ORACLES and the CLoud-Aerosol-Radiation Interaction and Forcing: Year-2017 (CLARIFY-2017) field experiments have led to robust quantitative evaluations of satellite ACAOD (Jethva et al, 2018;LeBlanc et al, 2020;Peers et al, 2021;.…”
mentioning
confidence: 99%
“…The ORAC retrieval gives systematically lower τ values than the Peers retrieval (Figures 4b, 4d, and 4f). This low bias is small on the first day and larger on the second day, when it assumes values that are by and large consistent with an underestimation of 35% caused by ignoring above‐cloud aerosol (Peers et al., 2021).…”
Section: Resultsmentioning
confidence: 85%